Toward the Construction of a Federal Policy-Impact Code for Classifying the Nation's Rural School Districts: A Response to Stephens, Reeder, and Elder - Paul M. Nachtigal (Journal of Research in Rural Education, 1992)
The papers by Stephens, Reeder, and Elder represent a significant milestone in the ongoing saga of giving definition to that sector of the elementary-secondary educational enterprise known as rural education. The necessity of giving definition to rural education has grown as public education has become more and more urbanized. At the point when America was primarily a rural agrarian nation, public education was, with few exceptions, rural education.